Effectiveness of Online Learning for Practical Course of Graphic Design - Abdul Majid, Basrul (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2024)
The Covid-19 outbreak is spreading rapidly among the world's population. To prevent the virus, the government has adopted a social distancing policy. This pandemic situation has kept Indonesians at home. The learning process continues with the help of the internet and educators. Then, the students do not need to be at school for face-to-face direct learning. UIN Ar-Raniry continues to conduct online teaching and learning activities using e-learning media such as Google Meet, Zoom, Google Classroom, and YouTube. This study examines the effectiveness of online learning and the results of face-to-face online learning in graphic design practicum courses. This research uses quantitative methods. Data was collected by distributing questionnaires online to students in 2018 and 2017 and was processed using the SPSS program. The research results obtained show a practical value of 0.012 (sig < 0.05) for online learning in 2018 and 0.000 (sig < 0.05) for face-to-face learning in 2017, but some students experience difficulties in online learning.